Motor Learning Improvement Remains 3 Months After a Multisession Anodal tDCS Intervention in an Aging Population - Dumel, Gaëlle; Bourassa, Marie-Eve; Charlebois-Plante, Camille; Desjardins, Martine; Doyon, Julien; Saint-Amour, Dave; De Beaumont, Louis (Frontiers in Aging Neuroscience, 2018)
Healthy aging is associated with decline of motor function that can generate serious consequences on the quality of life and safety. Our studies aim to explore the 3-month effects of a five-day multisession anodal transcranial direct current stimulation (a-tDCS) protocol applied over the primary motor cortex (M1) during motor sequence learning in elderly. The present sham-controlled aging study investigated whether tDCS-induced motor improvements previously observed 1 day after the intervention persist beyond 3 months. A total of 37 cognitively-intact aging participants performed 5 consecutive daily 20-minute sessions of the serial-reaction time task (SRTT) concomitant with either anodal (n=18) or sham (n=19) tDCS over M1. All participants performed the Purdue Pegboard Test and transcranial magnetic stimulation measures of cortical excitability were collected before, 1 day after and 3 months after the intervention. The last follow-up session also included the execution of the trained SRTT. The main findings are the demonstration of durable effects of a 5-day anodal tDCS intervention at the trained skill, while the active intervention did not differ from the sham intervention at both the untrained task and on measures of M1-disinhibition. Thus, the current paper revealed for the first time the durability of functional effects of a-tDCS combined with motor training after only 5 days of intervention in an aging population. This finding provides evidence that the latter treatment alternative is effective in achieving our primary motor rehabilitation goal, that is to allow durable motor training effects in an aging population.